Design and simulation of rotated hexagonal porous core photonic crystal fibre with improved effective material loss and dispersion properties - Izaddeen Kabir Yakasai; Pg. Emeroylariffion Abas; Norazanita Hj Shamsuddin; Feroza Begum (Institute of Advanced Engineering and Science, 2020)
A thorough modal characterization, centred on the full vectorial finite element method (FEM) has been used to model and numerically investigate a porous core photonic crystal fibre (PC-PCF), which may potentially be integrated into Terahertz (1012 Hz) compact systems. The proposed fibre consists of a rotated hexagonal core surrounded by a conventional hexagonal cladding. It has been shown that effective material loss (EML), core power fraction and dispersion profile are 0.019 cm-1, 51.7% and 0.5 ± 0.04 ps/THz/cm within 1 THz bandwidth, respectively. Based on simulated results and noncomplex design, it is envisaged that the proposed fibre can be realised for industrial THz applications.